Croatian freshwater oligochaetes: species diversity, distribution and relationship to surrounding countries - Kerovec, Mladen; Kerovec, Maja; Brigić, Andreja (Zootaxa, 2016)
This paper presents a checklist of the freshwater oligochaetes of Croatia, including data related to the ecoregions, river basins and habitat types in which species were recorded. The checklist is based on literature data and new records from unpublished research conducted since 1975. A total of 71 freshwater oligochaete species were recorded at 345 sampling sites. The family Naididae was most species rich (31 species), followed by the family Tubificidae (27 species), Lumbriculidae (6 species) and Pristinidae (4 species). The families Haplotaxidae, Propappidae and Lumbricidae were least diverse, with only one species recorded for each. Approximately two-thirds of the oligochaete species occurred in both the Dinaric western Balkan and the Pannonian lowland ecoregions. Similar patterns in species richness were detected for the Black Sea and the Adriatic Sea basins. Species richness varied between habitat types, with rivers as the most speciose habitats. In comparison to adjacent countries, the Croatian oligochaete fauna was most similar to that of Bosnia and Herzegovina, Hungary and Austria.